2011
DOI: 10.4269/ajtmh.2011.11-0154
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Parameters in Pediatric Uncomplicated Plasmodium falciparum Malaria in Sub-Saharan Africa

Abstract: Hematologic changes in acute and convalescent uncomplicated Plasmodium falciparum malaria have not been well studied, particularly in young children in Africa. Hematologic data were obtained for 3,044 children less than five years of age in seven randomized controlled trials at 14 sites. Using paired analysis between day 28 and baseline in patients without parasitologic failure as a proxy for malaria-induced effects, we found a statistically significant but clinically modest increase in leukocyte counts (5%) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 20 publications
14
43
0
Order By: Relevance
“…by guest www.bloodjournal.org From been observed in thousands of uncomplicated malaria cases in both adults and children treated with artemisinin combined therapy. 35,36 Our observations also suggest that the persistent pattern may result from a more complex overlap of mechanisms that comprise those causing the 2 polar rising and PADH patterns (Figures 2 and 4). A monophasic, accelerated clearance of normal or uninfected erythrocytes has been observed in malaria patients in Thailand.…”
Section: Discussionmentioning
confidence: 63%
“…by guest www.bloodjournal.org From been observed in thousands of uncomplicated malaria cases in both adults and children treated with artemisinin combined therapy. 35,36 Our observations also suggest that the persistent pattern may result from a more complex overlap of mechanisms that comprise those causing the 2 polar rising and PADH patterns (Figures 2 and 4). A monophasic, accelerated clearance of normal or uninfected erythrocytes has been observed in malaria patients in Thailand.…”
Section: Discussionmentioning
confidence: 63%
“…Perhaps, a more large-scale survey is much more likely to be with little bias for severe malaria. Second, the absence of comparative data on widely reported monocytes and platelets detracts from the strength of this study (Erhart et al 2004;Quintó et al 2006;Olliaro et al 2011). Nevertheless, the strong association of low haemoglobin \11 g/dl in patients with P. falciparum infection, as compared to the others argues for recognition of low haemoglobin as an important predictor of malaria in febrile patients.…”
Section: Discussionmentioning
confidence: 91%
“…Most workers have looked at patelets, monocytes, haemoglobin, total white blood cell counts, neutrophils and lymphocytes (Erhart et al 2004;Quintó et al 2006;Olliaro et al 2011), and a few have reported on eosinophils and basophils (Maina et al 2010). Irrespective of the measured parameters, low haemoglobin \11 g/dl, low platelets \1.5 9 10 4 lL, high monocytes counts [1.5 9 10 3 lL and their combinations thereof, have had superior predictive capacity for P. falciparum infections in Sub-Sahara Africa (Quintó et al 2006;Oduro et al 2007;Adedapo et al 2007;Olliaro et al Fig. 2 Haemoglobin versus age distribution of (a) P. falciparum infected and (b) non-malaria infected aneamic children with Tricube kernel smooth fit line generated with local polynomial regression at 60 % of points to fit 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the aspects of the current world burden, control and epidemiology (Bell et al, 2005;Socrates, 2015;Olliaro et al, 2011). There are enormous literature resources to understand the clinical, socio-economic and political aspects of this disease.…”
Section: Introductionmentioning
confidence: 99%